Students’ Perception of the Use of Animation in Vocabulary Lessons of 8th Graders of SMPN 1 Atambua - Amkolo, Modesta; Syafitri, Widya (JOINT: Journal of Inspirational English Language Teaching, 2024)
Modern education is challenging since teachers are no longer the main source of information. Teachers are expected to fill the role of parents, friends, and counsellors. To fulfill this expectation, teachers need innovative teaching methods to assist them in going further, including involving assisting tools like interactive Animation to help them. This study examines how animated learning methods impact vocabulary acquisition among students in Atambua using the grounded theory method. Research and focus group discussions revealed that students prefer animated learning for its dynamic approach, enhancing engagement and imagination in vocabulary acquisition through the grounded theory method. The findings underscore how animated learning methods cater to individual learning needs and styles, fostering creativity and critical thinking in vocabulary acquisition. Furthermore, animated learning creates a supportive environment for problem-solving and resilience development, emphasizing the importance of embracing challenges for student growth. Overall, this study emphasizes the value of alternative learning methods in creating inclusive and effective educational experiences, preparing students for success in the modern world.